BENTUK AFIKSASI RAGAM BAHASA REMAJA DALAM NOVEL MARMUT MERAH JAMBU KARYA RADITYA DIKA - Mulyani, Wahyu (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
The purpose of this study was to describe about: 1) forms the prefixs to the mark language diversity in Marmut Merah Jambu novel works Raditya Dika, 2) forms suffixes that mark the language diversity in Marmut Merah novel works Raditya Dika. The method used descriptive, qualitative approach, data collection methods see and record. The research found that affixes the prefix form there are two types of di- and nge-. Prefix language diversity was a teenager the same function as the prefix di- in Indonesian that raw form a passive verb. Prefix nge- synonymous with the prefix meN- in Indonesian profound, but the change in shape adapted to the words that follow and functions to form an active verb. Suffix forms found in four types: -in, -i, nya, -an. Suffix -in suffix synonym with suffix -kan in Indonesian. Its function is twofold can form a transitive verb and a verb intransitive. Transitive verb requires an object, being verb intransitive object does not appear. Suffix -i, nya, and -an, synonymous suffix -i, nya, -an Indonesian. Suffix -in which form the verb monotransitive, because it has one object. Suffixes –nya to form words task. Suffix -an forming a passive verb.